Identification of CS Degradation Products in Objects Delivered from the Zone of a Special Military Operation - A. S. Iarlychenko; V. A. Ignatev; M. A. Ponsov; A. M. Grigoryev (Вестник войск РХБ защиты)
The formation of a CS aerosol during the combustion of a pyrotechnic mixture in gas grenades is accompanied by the formation of numerous thermolytic degradation products. Many of these products (including CS itself) are highly reactive substances, as a result of which the composition of the aerosol differs significantly from the set of products that can be subsequently detected in environmental objects.The aim of the work is to detect and identify CS derivatives in soil samples and in the material of gas grenades delivered from the zone of a special military operation to assess their relative content and select promising markers of the fact of CS use.Research methods. Detection and structural identification of CS degradation products were performed using gas and liquid chromatography-mass spectrometry (lowand high-resolution).The results of the study. More than 30 compounds have been found that are products of oxidation, reduction, thermochemical degradation and dimerization of CS and its derivatives. The method of liquid chromatography-mass spectrometry, which was not previously used for such work, presumably identified five compounds, information about which in relation to gas grenades is not available in the sources available to us.Conclusion. In the case of object analysis by gas chromatography-mass spectrometry, the most convenient marker of CS exposure is 2-chlorobenzylmalonyl nitrile, while the content of CS itself may be insignificant. For the variant of analysis by liquid chromatography-mass spectrometry, it is preferable to search for products of cyclization of CS of quinoline origin (positive ionization mode), and for the negative mode products of dimerization and reduction of CS.